HUMOR TERKAIT MU’AMMAR AL-QAŻĀFI (ANALISIS PRAGMATIK) - Saputro, Septian (Adabiyyāt: Jurnal Bahasa dan Sastra, 2016)
Humour functions as a critic, satire, irony or propaganda. By using humour, it is posible to say the truth elegantly and sofly, without disturbing others’ feeling. In pragmatic comunication theory, humour is created from deviations of comunication principles, e.g: Grice principle of comunication and Leech principle of comunication. This research uses the jokes on the former leader of Libyan Mu’ammar al-Qażāfi as the object material. Mu’ammar al-Qażāfi was the leader of controversy as well as he was a dictator. Then, there are assumptions that the humours about al-Qażāfi are not only about entertaiment but also about special aims. The researcher uses pragmatic analysis that covers Grice cooperative principle, Leech politeness principle and speech acts (illocutionary act). The results are that political humour in Libyan was a new kind of humour and it was developed while the revolution was on and in the aftermath. While Ilocutionart Acts, which are found in the humours about al-Qażāfi, are irony, claiming, ordering, complaining, and satiring. The aims in the humours are satire and irony.